2007
DOI: 10.1110/ps.062358007
|View full text |Cite
|
Sign up to set email alerts
|

Structure, interactions, and dynamics of the RING domain from human TRAF6

Abstract: A key step in the signaling cascade responsible for activation of the transcription factor NF-kB involves Lys63-linked polyubiquitination of TRAF6. Covalent attachment of ubiquitin (Ub) to TRAF6, and subsequent poly(Ub) chain synthesis, is catalyzed by the hUev1a-hUbc13 heterodimer. hUbc13 is a catalytically competent E2 enzyme, and hUev1a is an E2-like protein that binds substrate Ub. The hUev1a-hUbc13 heterodimer is targeted to TRAF6 through interactions between hUbc13 and the N-terminal RING domain from TRA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 100 publications
(147 reference statements)
0
33
0
Order By: Relevance
“…Previous structural studies using NMR revealed that the RING domain (residues 67-124) of TRAF6 presents a topology similar to those of other RING domains, indicating that the RING adopts a correctly folded structure in the absence of ZF1 (30). Interestingly, the NMR structure of TRAF6 RING revealed a very weak affinity for Ubc13 in the low millimolar range (30), which is too weak to be biologically relevant. This result suggests that other regions contiguous to the RING and possibly the first ZF domain may serve to increase the affinity of TRAF6 for Ubc13.…”
Section: Zf Domains 2-4 Are Dispensable For Interacting With Nemo-inmentioning
confidence: 95%
“…Previous structural studies using NMR revealed that the RING domain (residues 67-124) of TRAF6 presents a topology similar to those of other RING domains, indicating that the RING adopts a correctly folded structure in the absence of ZF1 (30). Interestingly, the NMR structure of TRAF6 RING revealed a very weak affinity for Ubc13 in the low millimolar range (30), which is too weak to be biologically relevant. This result suggests that other regions contiguous to the RING and possibly the first ZF domain may serve to increase the affinity of TRAF6 for Ubc13.…”
Section: Zf Domains 2-4 Are Dispensable For Interacting With Nemo-inmentioning
confidence: 95%
“…( b , c , d , e ) TRIM56 RING domain was aligned with various closely related RINGs showing the clashes (circled) of SopA with the central α-helix of various RING domains ( b , TRIM32; c , TRAF6; d , RNF4; e , TRIM39). PDB codes of the structures used in the alignment are indicated in brackets: (2JMD)47, (4AP4)30. ( f ) SopA does not bind TRIM32, TRIM39 and RNF4.…”
Section: Figurementioning
confidence: 99%
“…The TRAF-C domain mediates receptor binding to TNFR superfamily members (50,51), and the absence of this domain abolishes TRAF6 binding to members of this superfamily (29,54,55). Interestingly, the TRAF6 TRAF-C domain is not required for several important CD40-mediated TRAF6-dependent events, indicating that CD40 may use TRAF6 as a strictly CY adaptor protein in certain situations (29), similar to TRAF6 use by the Toll-like receptors (44).…”
Section: Volume 286 • Number 12 • March 25 2011mentioning
confidence: 99%